Layoff Worker Efforts to Meet the Families Needs During the Covid-19: Indonesian Marriage Law Perspective - Musyafaah, Nur Lailatul; Luthfi F, Dista Nada; Apriliyana, Daning Dwi; Rahman, Kharisma Aulia (Alhurriyah, 2023)
During the Covid-19 pandemic, many workers experienced layoffs, as experienced by some residents of the Takeran District. Layoffs have an impact on the family's economy. This article discusses workers' efforts to be laid off to meet their families' needs during the Covid-19 pandemic. The research is conducted in Takeran, Magetan, East Java, Indonesia. Data is collected through interviews with three families, observation in Takeran, and documentation about the worker's efforts, and then it is analyzed using descriptive analysis. The study showed that the workers’ layoffs during the Covid-19 pandemic affected their families' economic conditions. They switched professions to meet their families' needs; some became farmworkers, vegetable sellers, and online motorcycle taxi drivers. Their income is insufficient for their needs, so their wives work to help the family economy. Their efforts can meet the needs of families during this pandemic..Pada masa pandemi Covid-19 banyak pekerja yang mengalami PHK, sebagaimana yang dialami beberapa warga Kecamatan Takeran Kabupaten Magetan Provisi Jawa Timur, Indonesia. Hal tersebut berimbas pada pemenuhan kebutuhan ekonomi keluarga. Artikel ini membahas tentang upaya korban pemutusan hubungan kerja untuk memenuhi kebutuhan keluarga pada masa pandemic Covid-19. Penelitian ini adalah penelitian lapangan yang dilakukan di Takeran, Magetan, Jawa Timur, Indonesia. Data dihimpun melalui wawancara, observasi dan dokumentasi. Data yang terkumpul dianalisis dengan menggunakan teknik analisis deskriptif dengan menggunakan pola pikir deduktif. Hasil penelitian menimpulkan bahwa korban PHK di masa pandemi Covid-19 mempengaruhi kondisi perekonomian keluarga. Karena itu suami beralih profesi untuk tetap memenuhi kebutuhan rumah tangga, ada yang menjadi buruh tani, penjual sayur dan driver ojek online. Penghasilan tersebut kurang mencukupi kebutuhan keluarga maka istri bekerja membantu perekonomian keluarga. Kerjasama tersebut mampu memenuhi kebutuhan keluarga pada masa pandemic ini.